OP0135 Erectile Dysfunction is Common among Gout Patients. (10th June 2014) - Schlesinger, N.; Radvanski, D.C.; Fischkoff, J.; Kostis, J.B.
Abstract : Background: Erectile dysfunction (ED) is common in the general population. The likelihood of ED increases progressively with age; however, it is not an inevitable consequence of aging. The importance of vascular disease as an underlying cause of ED is well established. Patients who present with ED have an increased rate of cardiovascular disease (CVD) risk factors and concomitant silent coronary artery disease (CAD). Gout and hyperuricemia are commonly associated with CVD risk factors and CAD. Objectives: To determine whether men with gout may have an increased prevalence of ED as compared to men without gout. Methods: In this cross sectional study, men aged 18-89 presenting to the Rheumatology clinic between 8/26/10 and 5/13/2013, were asked to participate. The presence of ED was determined by filling out a Sexual Health Inventory in Men (SHIM). The SHIM classifies ED into one of five categories: absent (26–30), mild (22–25), mild to moderate (17–21), moderate (11–16) and severe (1–10). The patient's history, physical examination and recent laboratory studies were reviewed as well. Descriptive statistics and subgroup analyses were used to summarize the data. We used chi-square tests for independence to compare categorical variables. Results: Of the 201 men surveyed 83 had gout. A significantly greater proportion of gout patients had ED (n=63;76%) compared with patients without gout (n=61;52%) (p=0.0007). A significantly greater proportion of gout patients (43%) had severe ED compared with patients without gout (30%) (p=0.007). The mean SHIM score of all patients was 16.88 (SD ±-0.83). Gout patients had an average SHIM score of 14.38 (SD ±1.01) versus 18.53 (SD ±0.964) in patients without gout (p<0.0001). A significantly greater proportion of gout patients whose age was ≥65 had ED versus patients without gout (p=0.0001) and it was significantly more likely to be severe ED versus patients without gout (p=0.0002). A significantly greater proportion of patients with tophaceous gout had ED versus those without tophi (p=0.0001). In a multivariate analysis the association between gout and ED remained statistically significant even after adjusting for age (p=0.0009), hypertension, LDL, GFR, obesity, depression (p=0.0154) and diabetes (p=0.0085). Conclusions: ED is present in most men with gout and is frequently severe. Increasing awareness of the presence of ED in gout patients may lead to earlier medical attention and treatment as well as evaluation of possible silent CAD. We propose that all men with gout be routinely screened for ED. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.1156